A Microservice-driven Collaborative Agent in Virtual Learning Environments: A Role Model for a Tracing Agent - Thalheimer, Jéferson Miguel; Haendchen Filho, Aluizio; Briks, Fabio Julio Pereira; Ribeiro, Rafael Castaneda; Concatto, Fernando; Viecelli, Angélica Karize (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
Currently, distance learning comprises almost half of students enrolled in undergraduate courses in Brazil. However, the dropout rate of this modality is over 50%, and only 22% of students complete the courses [27]. Despite technological advances and good acceptance of this modality, research indicates that the lack of involvement in a virtual community can lead to feelings of loneliness, low selfesteem, isolation and desmotivation. There is evidence that these feelings are among the main factors responsible for the low performance and high evasion rate. Virtual Learning Environments (VLE) handles a large volume of student interaction data. In this context, it is important to create mechanisms to maintain and manage a data structure to facilitate the processes of transforming data into information and knowledge. This paper aims to present a tracing agent responsible for maintaining and managing the data structure in VLE. The agent acts in the context of a microservice-oriented multi-agent system, interacting and collaborating with other agents in order to improve interaction and decision-making processes. This work becomes original and at the same time innovative, presenting an unprecedented combination of technologies and techniques in the context of VLEs.